2013
DOI: 10.1186/1756-0500-6-57
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ceftizoxime for elective cesarean delivery at Soba Hospital, Sudan

Abstract: BackgroundA prophylactic antibiotic is recommended to reduce infection-related complication following cesarean delivery. There is a current debate on the time of prophylactic antibiotic in cesarean delivery.MethodsAn opened randomized, controlled clinical trial was conducted at Soba hospital, Sudan to investigate the timing (pre-incision or after clamping of the umbilical cord) of ceftizoxime for elective cesarean delivery. The outcome measures were; the incidence of post-cesarean febrile and infection-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…We included 18 RCTs comparing the application of prophylactic antibiotics before vs. after cord clamping (13,(17)(18)(19)(20)(21)(22)(23)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were conducted in the USA (17,20,29,(32)(33)(34)(35), Turkey (37), Austria (36), India (28,30), Iran (18,21), Egypt (31), Tunisia (19), Sudan (22), Italy (23) and China (13). The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We included 18 RCTs comparing the application of prophylactic antibiotics before vs. after cord clamping (13,(17)(18)(19)(20)(21)(22)(23)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were conducted in the USA (17,20,29,(32)(33)(34)(35), Turkey (37), Austria (36), India (28,30), Iran (18,21), Egypt (31), Tunisia (19), Sudan (22), Italy (23) and China (13). The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1. In brief, 13 studies included women with elective cesarean section solely (13,(17)(18)(19)(20)22,(29)(30)(31)(32)(33)36,37), two studies reported that more than 75% of women received elective cesarean section (21,28), and three studies were focused on non-elective cesarean section (23,34,35). The majority of studies administered a first-generation cephalosporin (cefazolin 1 g, cefazolin 2 g or cefathiamidin 2 g) (13,18,19,21,29,(31)(32)(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations